INTERNALISASI NILAI-NILAI RELIGIUS MELALUI PEMBIASAAN KEAGAMAAN DI MI HIJRIYAH II PALEMBANG - Ayu Natasya, Reska; Nurlaeli; Husni, Miftahul; Aquami; Fatmawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the process of internalizing religious values ​​through religious habits and the problems faced at MI Hijriyah II Palembang. The study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that internalization of religious values ​​is carried out through routine and continuous religious habits, including reading the Qur'an, daily prayers, Islamic etiquette habits, Yasinan, and memorization of short surahs. This process is able to shape the values ​​of faith, worship, morals, social and tolerance, as well as discipline and responsibility of students. However, its implementation still faces obstacles such as differences in student character and motivation, time constraints, lack of consistency, and environmental influences and parental support. The success of internalization is greatly influenced by the consistency of habits, the role of teachers, and family support.